The Educational Resource Management According to Opinions of Personnel at the Border Patrol Police School Border Patrol Police Division 21 - Ngamlers, Siriporn; Sangngern, Supod; Wisetsri, Suparp; Pitilerdsirikul, Napatthika; Watanawong, Suwat (Arts of Management Journal, 2024)
This article aimed to study (1) educational resource management according to the opinions of personnel at the Border Patrol Police School. Border Patrol Police Division 21 (2) compares the management of educational resources according to the views of personnel at the Border Patrol Police School, classified by gender, work experience, and education level. (3) Guidelines for developing educational resource management according to the opinions of personnel at the Border Patrol Police School. The sample consisted of the headmaster and teachers at the Border Patrol Police School. They were selected by comparing the Krejcie and Morgan ready-made tables and comparing the proportions, which were obtained through purposive selection. The instrument for collecting is a 5-level rating scale questionnaire, and it is a structured discussion group (focus group). Descriptive statistics and content analysis are used to analyze the data. The research results were found as follows: 1) Management of educational resources according to the opinions of personnel at the Border Patrol Police School, overall, there is a high level of compliance. When considering each aspect, it was found that the aspect with the highest average was human resource management. 2) Comparative results of educational resource management at Border Patrol Police Schools Classified by work experience and education level, overall each aspect was not different, classified by gender. Overall, there was no difference when considering each aspect. It was found that resource management in terms of materials and equipment was significantly different at the .05 level. 3) Guidelines for developing educational resource management: according to the opinions of patrol police school personnel, it was found that they are police but act as teachers; there are many agencies involved in the work; carrying out 8 projects under the royal initiative; unrelated qualifications; having educational qualifications lower than a bachelor’s degree; and managing limited educational resources for maximum benefit.